A randomised trial of glucocorticoids in acute-stage allergic bronchopulmonary aspergillosis complicating asthma. Issue 2 (19th November 2015) - Agarwal, Ritesh; Aggarwal, Ashutosh N.; Dhooria, Sahajal; Singh Sehgal, Inderpaul; Garg, Mandeep; Saikia, Biman; Behera, Digambar; Chakrabarti, Arunaloke
Whether use of high-dose steroids in acute-stage allergic bronchopulmonary aspergillosis (ABPA) is associated with superior outcomes is not known. Herein, we compare the efficacy and safety of two glucocorticoid protocols in ABPA. Treatment-naive ABPA subjects randomly received either high-dose or medium-dose oral prednisolone. The primary outcomes were exacerbation rates and glucocorticoid-dependent ABPA after 1 and 2 years, respectively, of treatment. The secondary end-points were composite response rates after 6 weeks, improvement in lung function, time to first exacerbation, cumulative dose and adverse effects. 92 subjects (high-dose n=44, medium-dose n=48) were included in the study. The numbers of subjects with exacerbation after 1 year (high-dose 40.9% versus medium-dose 50%, p=0.59) and glucocorticoid-dependent ABPA after 2 years (high-dose 11.4% versus medium-dose 14.6%, p=0.88) were similar in the two groups. Although composite response rates were significantly higher in the high-dose group, improvement in lung function and time to first exacerbation were similar in the two groups. Cumulative glucocorticoid dose and side-effects were significantly higher in the high-dose group. Medium-dose oral glucocorticoids are as effective and safer than high-dose in treatment of ABPA. Medium-dose glucocorticoids are as effective as high-dose in treatment of allergic bronchopulmonary aspergillosis http://ow.ly/TLt4N